Evaluation of water quality impact on the compressive strength of concrete - Ikpa, C.C.; Alaneme, G.U.; Mbadike, E.M.; Nnadi, E.; Chigbo, I.C.; Abel, C.; Udousoro, I.M.; Odum, L.O. (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research presents the influence of mixing-water quality on the compressive strength properties of concrete using secondary and tertiary waste water treatment source, borehole and distilled water sources. Popular criteria for water quality assessment for concrete works involves the impression that once it is fit for consumption or drinking, it is therefore suitable for concrete works while other alternatives are suitability of the water used in terms of being clean and free from deleterious substances. However, these requirements may not provide a water suitability evaluation baseline for concrete works because some water quality which do not meet up with these requirements have been observed to produce satisfactory results in terms of strength and durability property performance of concrete. Statistical comparative-analysis techniques are required to evaluate the effects of water from control or referenced source of absolute quality with those of questionable quality so as to validate its usage for concrete works. The physiochemical characteristics of the water samples were ascertained before they were utilized for the concrete production and the setting time characteristics were derived, showing longer setting time results SWWT and TWWT due to high level of COD compared to DW and BW. The concrete samples produced were cured for varying hydration periods ranging from 7 – 28 days and their respective compressive strength values obtained in the laboratory. From the results, distilled water produced a maximum average compressive strength of 17.96 N/mm2 while secondary wastewater source produced the minimum results of 12.09 N/mm2. Statistical evaluation was carried out on the experimental data using ANOVA and Dunnet post-hoc test to validate the experimental findings and the details derived from the computations explains the importance of ascertaining the quality of water used for concrete production so as to achieve better overall concrete performance in terms of mechanical and durability properties.